2020
DOI: 10.1186/s12885-020-07380-5
|View full text |Cite|
|
Sign up to set email alerts
|

A pilot study of improved psychological distress with art therapy in patients with cancer undergoing chemotherapy

Abstract: Background Art therapy may improve the physical, mental, and emotional wellbeing of individuals for a variety of purposes. It remains understudied and underutilized in cancer care. We sought to determine the ability of a pilot art therapy program to improve the physical, mental, and emotional well-being of cancer patients. Methods Chemotherapy-recipients, age 18 years and older, diagnosed with any type or stage of cancer, were considered eligible to participate in this single arm, pilot study, using four vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…To the best of our knowledge, this is the rst study to investigate the in uence of waiting room ambiance on the anxiety level of non-metastatic cancer patients before chemotherapy. Other studies have investigated metastatic patient groups, implemented interventions directly on the patients and not the waiting environment, or the anxiety during chemotherapy was investigated [32,45]. In conclusion, we have concluded that visual and audial interventions in waiting rooms may reduce the anxiety level of patients scheduled to experience chemotherapy for the rst time.…”
Section: Discussionmentioning
confidence: 68%
“…To the best of our knowledge, this is the rst study to investigate the in uence of waiting room ambiance on the anxiety level of non-metastatic cancer patients before chemotherapy. Other studies have investigated metastatic patient groups, implemented interventions directly on the patients and not the waiting environment, or the anxiety during chemotherapy was investigated [32,45]. In conclusion, we have concluded that visual and audial interventions in waiting rooms may reduce the anxiety level of patients scheduled to experience chemotherapy for the rst time.…”
Section: Discussionmentioning
confidence: 68%
“…Further, it is a novel therapy that utilizes the creative process to help individuals explore their feelings and emotions, providing new methods to gain personal insight and develop coping skills ( Malik, 2021 ). This therapy is reported to be highly effective in elevating the psychological burdens of a wide range of chronic diseases, such as cancer, multiple sclerosis, and stroke ( Elimimian et al, 2020 ; Kline, 2016 ; Newland et al, 2020 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Overall, art therapy is recognized as an intervention that enhances the mind–body connection and, in turn, reduces the levels of physical and psychological stressors ( Elimimian et al, 2020 ; Malchiodi, 2003 , 2020 ; Newland et al, 2020 ). Mind–body-related interventions have been described in a wide range of health-related psychology disciplines, such as sports psychology ( Henning Schöttke & Giabbiconi, 2015 ; Schöttke et al, 2020 ), medical psychology, and spiritual psychology ( Lusebrink, 2010 ; Silverstone, 2009 ; Winkelman & Sessa, 2019 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Providing integrated care that is directed to the overall wellness of the patient, maximizes the potential to increase patient satisfaction, increase patient medical compliance, and preserve quality of life [85][86][87]. Interestingly, it has also been found that ethnic minority groups, who typically report poorer quality of life and worse distress after diagnosis, may derive more acute benefit from integrated modalities like art therapy [88]. It is also of importance to note that effective psychosocial support programs have been shown to be significantly associated with favorable clinical outcomes [84,[89][90][91][92].…”
Section: Clinical Considerations Of a Growing Cohort Of Long-term Surmentioning
confidence: 99%